Study of Physical, Chemical, and Sensory Characteristics of Modified Square Banana Flour (Musa balbisiana) - Muhammad Nur Buwono; Bambang Sigit Amanto; Esti Widowati (Indonesian Association of Food Technologists, 2018)
Amylose content related to the glycemic index, the higher the content of amylose the lower the glycemic index thus good for diets. Starch modification through fermentation using lactic acid bacteria can be used to increase amylose. In this experiment, modification of Square banana (Musa balbisiana) flour was conducted using Lactobacillus fermentum at certain concentration and fermentation time. This study used a Completely Randomized Factorial Designs (CRFD) with variation of fermentation time (24 hours, 48 hours, 72 hours) and concentration of bacteria starter (0.125%; 0.250%; 0.375% v/v) as the factor. Data were statistically analyzed using Two-Way ANOVA. The results showed that the variation of fermentation time and concentration of starter change physical, chemical, and sensory characteristic of the flour. Water absorption, protein content, and amylose content were increased. However whiteness index, swelling power, solubility, and moisture content were decreased. Pasting properties was change significantly after this modification process. Meanwhile, antioxidant activity and sensory characteristics did not significantly change. In conclusion, the characteristics of the modified flour offer opportunities for the development of square banana flour-based food products with high amylose which good for the diet.